Alzheimer's Disease‐Related Polygenic Risk Score Profiles and Brain Proteinopathies. (20th December 2022) - Katsumata, Yuriko; Abner, Erin L; Kryscio, Richard J; Schmitt, Frederick A; Fardo, David W.; Nelson, Peter T
Abstract: Background: Genome‐wide association studies (GWAS) have identified more than 70 genetic loci significantly associated with Alzheimer's disease (AD). AD‐associated genetic variants have been mapped to biological pathways including endocytosis, oxidative stress, immune response, synaptic plasticity, lipid metabolic, apoptotic process, and amyloid‐beta formation. These diverse biological pathways may be differentially responsible for brain pathologies and combinations of proteinopathies. Pathway‐specific polygenic risk scores (PRSs) are useful to estimate an individual's genetic liability according to well‐characterized biologic pathways. In this study, we investigated differences in AD‐PRSs calculated by biological pathways in different brain proteinopathies. Method: Participant data comprised autopsied volunteers from the National Alzheimer's Coordinating Center (NACC) database linked to Alzheimer's Disease Genetics Consortium (ADGC) genotype data. We obtained Gene Ontology (GO) terms listed for Homo sapiens and mapped genes to each of the GO terms. Of 18, 826 GO terms, 7, 300 biological processes were extracted among those constructed of 3 or more genes. We also obtained AD‐related GWAS summary statistics from Kunkle et al. (2019; PMID 30820047). We then extracted single nucleotide polymorphisms (SNPs) with p <0.5 that were not located near the APOE loci. We examined the associations between biological pathway‐specific PRSs and proteinopathies using the Kruskal Wallis non‐parametric test. Result: ADGC genotype data were available for 1, 610 NACC participants. There were 4, 866 biological processes that had GWAS summary statistics from at least five SNPs. The distributions of "negative regulation of amyloid‐beta formation" PRSs were significantly different between A scores (Thal phase ratings for Aβ distribution: A0 = Phase 0, A1 = Phase 1 or 2, A2 = Phase 3, and A3 = Phase 4 or 5). The top three biological processes for B score (Braak NFT stage: B0 = Stage 0, B1 = Stage I or II, B2 = Stage III or IV, and B3 = Stage V or VI) were "cell differentiation", "signal transduction", and "protein transport". There was no significant biological pathway associated with TDP‐43 or Lewy body pathologies. Conclusion: Distinct brain proteinopatholies are likely caused by disruption of unique, albeit correlated, biological pathways. Further studies that integrate genetic information with PRSs may elucidate the mechanisms underlying brain proteinopathies.